Revisiting the Natures of War: Aegean Islands and the Ecologies of Displacement during the Civil War (1946-1949) - Bormpoudakis, Dimitrios; Bourlessas, Panos (Annals of the American Association of Geographers, 2022)
Military geographies have engaged with the subject of nonhuman nature in diverse and fruitful ways, mainly under the analytics of environment, landscape, territory (and terrain), and the more-than-human. Despite the diversity of contexts studied, spaces of displacement have not drawn scholarly attention within this literature. Starting from the position that human-nonhuman relations are emplaced, we offer an exploration into the natures of forced displacement during war. Specifically, we show that by extending our vision to spaces of displacement, we can see militarized nature under new, including more hopeful, lights. Drawing empirical material from the published memoirs of women and men displaced to the islands of the Aegean archipelago during the Greek Civil War (1946-1949), we make a twofold case. First, spaces of displacement should be seen as key in the study of militarized geographies, as they explode the ways militarized nature is understood to be reproduced. Second, nonhuman nature, in the context of the spaces of displacement, can act as a vector of emplacement, resistance, resilience, and reworking against the violence of the post-World War II liberal state.